Analisis Pengaruh Kebijakan Ekonomi Terhadap Kesejahteraan Mahasiswa - Yosep Moan Banda; Maria Klaret Ngina (Program Studi Pendidikan Ekonomi FKIP Universitas Flores, 2025)
This research aims to analyze the influence of government economic policies on the welfare of students in Indonesia, specifically at Flores Ende University. . Student welfare is an important aspect in creating quality human resources. This research uses a qualitative descriptive approach with data collection techniques through in-depth interviews, observation and documentation studies. The research subjects were Flores University students from 2 study programs, namely the management study program and the economic education study program. The research results show that economic policies such as the Indonesia Smart College Card (KIP-K), fuel subsidy policies, inflation and fiscal policy have a significant influence on student welfare. The positive impact can be seen from increasing access to higher education through tuition assistance, however inflation and rising prices of basic necessities have a negative impact on students' purchasing power. This research recommends the need to synchronize economic policies with student needs and increase social assistance programs that are more targeted.